BELIEF IS PRIOR TO KNOWLEDGE. (13th April 2015) - Rose, David
Abstract Orthodoxy has it that knowledge is a composite of belief and non-mental factors. However, Timothy Williamson suggests that orthodoxy implies that the concept of belief is acquired before the concept of knowledge, whereas developmental data suggest the reverse. More recently, Jennifer Nagel reviews the psychological evidence, building a psychological case that the concept of knowledge emerges prior to belief. I assess the psychological state of the art and find support for the opposite conclusion. Overall the empirical evidence supports the orthodox view that the concept of belief is prior to the concept of knowledge.